KEBEBASAN KEHENDAK (FREE WILL) DAVID RAY GRIFFIN DALAM PERSPEKTIF FILSAFAT AGAMA - Victor Delvy Tutupary (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2016)
Free will is an individual ability to have full control of his or her act and decision without any pressure from others. The problem of free will emerge from the debate between those who believe the very existence of free will and those who against it (determinism). Griffin's ideas consists of process theology and postmodern theology. Process Theology is based on the concept of process, enjoyment, essential relatedness, incarnation, creative self-determination, creative self-expression, novelty, and God-relatedness. Postmodern theology is a critique for two stages of modern view with its dualistic-supernaturalistic and materialistic-atheistic character, and propose a constructive postmodern vision, based on anti-individualistic spirituality, organicism, transformative traditionalism, naturalistic panentheism, and post-patriarchal. Griffin's conception of free will is divided into cosmology, theology, and axiology freedom. In cosmology freedom, human are creatures with high level of freedom since the dominant poles of the soul in human beings have enabled us to have a free selfdetermination. In theology freedom, the nature of God that not “all-powerful” and the existence of creativity power within human had made us seize a true freedom. In axiology freedom, human have freedom to form the ideal values based on sympathy and pluralism that renounce absolute truth claim, reject religion uniformity, and focus on deep dialogue.